ACTION for Men: Study Protocol of a Community Capacity Building Intervention to Develop and Implement Gender-Sensitive Physical Activity Programs for Men 50 Plus - Strobl, Helmut; Brew-Sam, Nicola; Curbach, Janina; Metz, Boris; Tittlbach, Susanne; Loss, Julika (Frontiers in Public Health, 2020)
Introduction: Capacity building for health promotion is a relevant precondition for sustainable, health-related changes in community settings. So far, there are few evidence-based recommendations about how to implement and evaluate community capacity building approaches. ACTION for men (A4M) is a project designed to build and evaluate capacities for health promotion in three rural communities in Bavaria, Germany, via a participatory approach including multiple community stakeholders. The project specifically aims at improving physical activity (PA) in men over 50 years of age (50 plus). Methods and Analysis: As a strategy to build the communities' capacities, we set up stakeholder groups in so far two communities. Those stakeholder groups will be facilitated over a period of 1–3 years. In regular meetings, the group members will be motivated to actively participate in planning and implementing PA programs for men 50 plus. The facilitation will systematically address key domains of community capacity (e.g., critical awareness, problem assessment, resource mobilization). The evaluation of the capacity building processes will be carried out using a mixed-methods design. Evaluation instruments consist of structured documentations and face-to-face interviews with stakeholder group participants (and drop-outs) as well as a pre-post-test using a standardized questionnaire in order to detect activity-related changes in men 50 plus from the involved communities. In community three, we will conduct the same procedure with a delay of 6 months. Discussion: Building community capacity for health promotion programs is the primary aim in A4M, and thus differs from previous research in which capacity is mostly a means to an end or an “incidental” result of a health promotion program. Therefore, A4M is expected to deliver important findings about how to implement and evaluate capacity building processes for health promotion, as well as how to address physical activity in community settings.